PENINGKATAN KESADARAN TENTANG KESELAMATAN KERJA DI RUMAH TEMPAT TINGGAL MELALUI SOSIALISASI DAN PELATIHAN SAFETY HOUSE DI RT 23 KELURAHAN BAGAN PETE KOTA JAMBI - Budi Aswin; Usi Lanita; Vinna Rahayu Ningsih (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Home is often considered the safest and most comfortable place for us. Everyone certainly thinks at home is the safest place. But without our knowledge, the house can also pose a danger when the occupants are active there. Domestic hazards and risks such as fire, food poisoning, dangerous goods, accidents, etc. Occupational Health and Safety (OHS) knowledge must be possessed by all families living at home, even though every day housewives and housemaids are basically people who live daily lives at home who need awareness about safety management. at home. In preparing for socialization activities and safety house training, it is necessary to establish Occupational Health and Safety (OHS) cadres in RT 23, Bagan Pete Village, Jambi City and increase the HR of these cadres through training. The training aims to make cadres and housewives understand and increase their awareness of the importance of the safety house in their daily activities at home. With these socialization and training activities, it is hoped that the understanding of Occupational Health and Safety (OHS) and safety houses for housewives can increase. Participants who received material on safety house socialization and training gained increased knowledge and awareness about work safety at home, which can be seen from the results of pre-test and post-test and statistically proven to have a significant effect. Characteristics Participants who participated in the safety house socialization and training were the majority of participants aged 27-34 years (63.3%), the most with high school education (83.3%) and the majority not working (76.7%). Keywords : Occupational Health and Safety (OHS), Safety House